Desarrollo de un sistema SCADA del invernadero experimental # 2 de la Universidad Técnica de Cotopaxi Campus Salache en el periodo 2021. - Anacleto Medina, John Jairo (2021)
This research study was carried out at the Technical University of Cotopaxi Campus Salache with the purpose of developing a SCADA system for monitoring the variables used in seedlings in greenhouse #2 for optimal development and production of crops. Therefore, a SCADA system was developed to monitor temperature, humidity and water level variables with a graphic interface. The system consists of electrical and electronic equipment such as PLC, electrical parameter analyzer Sentron PAC 2200, Simatic IOT 2040, humidity, temperature and flow sensors, which allow monitoring of the variables manually or automatically. The operation of the system consists of 3 solenoid valves distributed by sections, two 1 Hp pumps that will supply with the ideal pressure to optimize water consumption, the operation of the system was done through a graphical interface (HMI). Regarding the results, to obtain the humidity and temperature values, a hybrid sensor was connected to one of the rows of the greenhouse, and according to the data acquired, it is considered that the humidity value has a range of 89% and 11% which is practically zero humidity, the temperature shows a range that varies from 9 ºC to 20 ºC, and for the acquisition of electrical parameters such as voltage, current, frequency, power, a SIMATIC IOT 2040 was used, which are stored in a web server (Ubidots).